A numerical twist on the spin parameter, λR. Issue 1 (18th November 2018) - Harborne, K E; Power, C; Robotham, A S G; Cortese, L; Taranu, D S
ABSTRACT: A primary goal of integral field spectroscopic (IFS) surveys is to provide a statistical census of galaxies classified by their internal kinematics. As a result, the observational spin parameter, λ R, has become one of the most popular methods of quantifying the relative importance of velocity dispersion and rotation in supporting a galaxy's inner structure. The goal of this paper is to examine the relationship between the observationally deduced λ R and one of the most commonly used theoretical spin parameters in the literature, the Bullock et al. λ′. Using a set of N -body realizations of galaxies from which we construct mock IFS observations, we measure λ R as an observer would, incorporating the effects of beam smearing and seeing conditions. Assuming parameters typical of current IFS surveys, we confirm that there are strong positive correlations between λ R and measurement radius, and strong negative correlations between λ R and size of the PSF, for late-type galaxies; these biases can be reduced using a recently proposed empirical correction. Once observational biases are corrected for, we find that λ R provides a good approximation to 3/2 λ ^′ (R_eff), where λ′ is evaluated for the galactic stellar component within 1 R eff .